2013
DOI: 10.1111/jvim.12244
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of mRNA Expression of Surface Antigens between Histiocytic and Nonhistiocytic Sarcoma in Dogs

Abstract: Background: Definitive diagnosis of histiocytic sarcoma (HS) in dogs is relatively difficult by conventional histopathological examination because objective features of HS are not well defined.Hypothesis: Quantitative analysis of mRNA expression of selected cellular surface antigens (SAs) specific to HS in dogs can facilitate objective and rapid diagnosis.Animals: Dogs with HS (n = 30) and dogs without HS (n = 36), including those with other forms of lymphoma (n = 4), inflammatory diseases (n = 6), and other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Hemophagocytic HS originating from macrophages arises from splenic tissue. Dogs with HS (hereafter referred to as HS dogs) exhibit generally poor treatment outcomes because of the tumor's aggressive biological behavior, including its high cell proliferation, multidrug resistance, and metastatic potential (Yamazaki et al, 2013(Yamazaki et al, , 2014. Lomustine (CCNU) or doxorubicin have been commonly used as antitumor agents for HS dogs (Rassnick et al, 2010); however, the therapeutic benefit on the disseminated and hemophagocytic HS is insufficient because of resistance to these drugs (Klahn et al, 2011;Rassnick et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hemophagocytic HS originating from macrophages arises from splenic tissue. Dogs with HS (hereafter referred to as HS dogs) exhibit generally poor treatment outcomes because of the tumor's aggressive biological behavior, including its high cell proliferation, multidrug resistance, and metastatic potential (Yamazaki et al, 2013(Yamazaki et al, , 2014. Lomustine (CCNU) or doxorubicin have been commonly used as antitumor agents for HS dogs (Rassnick et al, 2010); however, the therapeutic benefit on the disseminated and hemophagocytic HS is insufficient because of resistance to these drugs (Klahn et al, 2011;Rassnick et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced survivin expression may play a role in the mechanism underlying chemoresistance acquisition (Rödel et al, 2012). We previously reported that suppressing survivin expression enhanced growth inhibition and CCNU sensitivity of canine HS cells (Yamazaki et al, 2013). These findings supported the hypothesis that survivin inhibition enhanced antitumor effects and chemotherapy efficacy.…”
Section: Introductionmentioning
confidence: 60%
“…For qRT-PCR assay, primers for survivin (5′-TCGAAGAGACCGCAAAGAAAGTGC-3′ and 5′-GAATTGTGGCCGTTCTCCTTTCCT-3′, 181 bp, GenBank accession number AY741504) (Yamazaki et al, 2013) and its internal reference hypoxanthine phosphoribosyltransferase 1 (HPRT; 5′-TGCTCGAGATGTGATGAAGG-3′ and 5′-TCCCCTGTTGACTGGTCATT-3′, amplicon size 192 bp, GenBank accession number NM001003357) were used. We performed qRT-PCR assays using a Rotor-Gene Q (Qiagen) and KAPA SYBR FAST qPCR Master Mix (KAPA Biosystems) according to the manufacturer's instructions.…”
Section: Survivin Expressionmentioning
confidence: 99%
See 2 more Smart Citations